SUPERVISI AKADEMIK KEPALA SEKOLAH SEBAGAI UPAYA MENINGKATKAN KINERJA GURU SDN 004 TOAPAYA DALAM PEMBELAJARAN DI KELAS - Mardiani, Rita (Jurnal Pembelajaran Prospektif, 2021)
This study aimed at improving the performance of SDN 004 Toapaya teachers in classroom learning through academic supervision at the second semester of the 2019/2020 academic year. The research subjects were teachers of SDN 004 Toapaya. The research was conducted in two cycles; each cycle consisting of four stages, namely: Planning, Implementing, Observing and Reflecting. The performance indicator set was if the score was at least 12 (sufficiently active). In classroom learning, it can be said that the actions taken are successful.Aspects measured in the observation are class teacher enthusiasm, teacher interaction with school supervisors, teacher interaction in KKG, group cooperation, and activities in group discussions. In the analysis, it was found that there was an increase in the activity and competence of teachers who compiled lesson plans from cycle I to cycle II. The achievement of performance indicators was achieved in the second action. Thus, it can be assumed that thePrincipal's Academic Supervision is an Effort to Improve the Performance of SDN 004 Toapaya Teachers in Classroom Learning. It is recommended to other supervisors or researchers that this teacher’s improvement model is continued to be implemented on an ongoing basis.